Microbial Biotechnology- A Laboratory Manual for Bacterial Systems - Das, Surajit (Springer, 2015)
Though tiny in size, bacteria impart many useful applications for the sustain able maintenance of the ecosystem on earth. On the evolutionary lineage, they are the first to appear and had plenty of time to adapt in the environmen tal conditions, subsequently giving rise to numerous descendant forms. They are omnipresent in huge number and their diversity is extended from hydro thermal vents to the cold seeps. These tiny, one-celled creatures carry out many useful functions and with the advancement of science, they have been explored greatly for use in food industry, agricultural industry, clinical sec tors and many others. Biotechnological industries utilise bacterial cells for the production of biological substances that are useful for human existence including foods, medicines, hormones, enzymes, proteins and nucleic acids. Despite huge benefits human beings gain out of these microscopic organisms, less attention has been paid to study these tiny creatures. Though the research on bacterial entities has gained momentum, it is estimated that only about 1% of the microorganisms have been discovered so far. However, rapid advances in molecular biology have revolutionised the study of bacteria in the envi ronment. It has provided new insights regarding their composition, phylog eny and physiology. New developments in biotechnology and environmental microbiology signify that microbiology will continue to be an exciting and emerging field of study in the future...